Meningkatkan Keterampilan Motorik Halus dengan Melipat Kertas Pada Kelompok B - Yuliani; Usman Afdal; Siti Nurhidayah Ilyas; Mulyadin Abdullah; Norma Sulistiyani; St. Aisyah Syahrani (STKIP Andi Matappa Pangkep, 2024)
This research is a Classroom Action Research, the subject of this research is 20 Group B children. The object of this research is fine motor skills using the Kemmis and Mc Taggart model. Data collection techniques were carried out using observation and documentation. The tool is an observation instrument sheet. Data analysis techniques are quantitatively descriptive. The expected success indicator is 95% of 20 children have fine motor skills. This research was conducted in two cycles. Based on the results of the study it can be concluded that through this activity one can improve fine motor skills in Group B at Al Azzam Islamic Kindergarten.